Privilege dan Insider: Ancaman Tersembunyi dalam Manajemen SDM - Wibowo, Purnomo Ari; Ngaijan, Ngaijan; Santoso, Kurniawan Teguh (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
"Insider" practices and "privileges" are often overlooked in human resource management (HRM) discourse, despite their significant impact on organizational justice, employee motivation, and overall performance. This article explores how informal connections and preferential treatment undermine meritocratic systems, distort perceptions of fairness, and reduce job satisfaction and employee commitment. Using a qualitative case study approach, the findings reveal that perceptions of injustice caused by informal practices—such as promotions based on personal ties, biased performance evaluations, and exclusive access to opportunities—can significantly weaken both intrinsic and extrinsic employee motivation. The study highlights the urgency of implementing transparent, accountable, and performance-based reward systems as strategic efforts to foster a fair and healthy organizational culture. Practically, organizations must develop HRM policies that are not only procedurally fair but also perceived as equitable to sustain long-term employee productivity and retention.